2014
DOI: 10.1186/1472-6882-14-381
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition, antioxidant, anti-wrinkles and tyrosinase inhibitory activities of cocoa pod extract

Abstract: BackgroundCocoa pod is an outer part of cocoa fruits being discarded during cocoa bean processing. Authors found out that data on its usage in literature as cosmetic materials was not recorded in vast. In this study, cocoa pod extract was investigated for its potential as a cosmetic ingredient.MethodsCocoa pod extract (CPE) composition was accomplished using UHPLC. The antioxidant capacity were measured using scavenging assay of 1,2-diphenyl-2-picrylhydrazyl (DPPH), β-carotene bleaching assay (BCB) and ferric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(59 citation statements)
references
References 59 publications
3
46
0
4
Order By: Relevance
“…The chromatogram(Figure 3)shows that vanillic acid (retention time: 9.17 min; peak area: 31.10%) was the phenolic antioxidant detected. The presence of quercetine and caffeic acid in the cocoa pods extract has been previously reported byKarim, Azlan, Ismail, Hashim, Abd Gani, et al (2014) andFapohunda and Afolayan (2012),…”
supporting
confidence: 77%
“…The chromatogram(Figure 3)shows that vanillic acid (retention time: 9.17 min; peak area: 31.10%) was the phenolic antioxidant detected. The presence of quercetine and caffeic acid in the cocoa pods extract has been previously reported byKarim, Azlan, Ismail, Hashim, Abd Gani, et al (2014) andFapohunda and Afolayan (2012),…”
supporting
confidence: 77%
“…Budiyanto et al [51] reported that olive oil topically applied after UVB exposure can effectively reduce UVB-induced murine skin tumors, possibly via its antioxidant effects in reducing DNA damage by reactive oxygen species, and that the effective component may be labile to UVB. This antioxidant activity presents high potential as a UVB sunscreen agent [10,52]. Argan oil can improve skin elasticity [53] and skin hydration by restoring the barrier function and maintaining the water-holding capacity [54].…”
Section: Discussionmentioning
confidence: 99%
“…Dakhil et al [57] have reported that safflower oil characteristics can make it a main ingredient in the preparation of topical agents for the treatment of various skin problems. Abdul Karim et al [52] recommended the possible use of cocoa pod extract as an ingredient in functional cosmetic products, specifically for anti-wrinkles as well as skin whitening or sunscreen products in combination with natural plant extracts to widen the spectrum of protection from sun rays.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study indicates that T. cacao extracts and gel both have a potent anti-microbial activity against various skin pathogens [93] [94] [95]. However, MIC values (Table 10) indicates that it has higher action against fungal strains than that of the bacterial strains [96].…”
Section: Discussionmentioning
confidence: 78%